KALINDAQDAQ IN THE KHATAM QURAN RITUAL OF THE MANDAR COMMUNITY: ANTROPOLINGUISTICS APPROACH - Nurhayati, Nurhayati (Prosiding Konferensi Internasional Kesusasteraan, 2025)
The Mandar people of West Sulawesi are rich in local culture. One such culture is kalindaqdaq. Kalindaqdaq is a type of Mandar poetry. The type of kalindaqdaq is adapted to the content of the kalindaqdaq, including educational kalindaqdaq, religious kalindaqdaq, entertainment or humor, and satire. Kalindaqdaq has various functions, one of which is as a means of communication for the Mandar people. Kalindaqdaq, as a means of communication for the Mandar people, is used in the ritual of completing the Quran. Children who have completed the Quran are mounted on dancing horses called sayyang pattuqdu. The child who has completed the Quran sits behind a jockey (passawe), usually a beautiful woman. Behind him is a parrawana (tambourine player) who plays the tambourine while playing the kalindaqdaq (makkalindaqdaq). The purpose of this study is to uncover the form and function of kalindaqdaq in the ritual of completing the Quran. The method used is the Simak method, with recording and note-taking techniques. Data analysis is descriptive.